Sociolinguistics - Spolsky, Bernard; New Mexico Univ., Albuquerque (Washington, D.C. : Distributed by ERIC Clearinghouse, 1998)
The development of literacy in selected bilingual societies was investigated. Historical and comparative studies were conducted of medieval Jewish communities, the Navajo community, a northern New Mexico village, and the countries of Paraguay and Tonga. The goal of the case studies was to develop a model for the development of literacy in the vernacular that can then be applied to the education of minority populations. Papers generated during the course of the studies are reprinted in nine chapters. The implications of the case studies for the choice of a language for initial literacy in bilingual education are discussed. It is concluded that a sociolinguistic model for vernacular literacy should include such factors as (1) the nature and language of literacy introduction, (2) the status of those accepting literacy, (3) the functions for which it is used, (4) the existence of political independence and control of the educational system, and (5) the continued use of the language. Necessary conditions for vernacular literacy include acceptance by traditionally influential members of the community, use for native functions, and maintenance by a locally controlled educational system. (RW)
Sponsoring Agency: National Inst. of Education (ED), Washington, DC. Teaching and Learning Program.
Glossary : P. 12Bibliographical references1-126. Includes
Policymakers.
Microfiche.
Keywords: Bilingual Education; Bilingualism; Case Studies; Guarani; Hebrew; Language Dominance; Language Planning; Language Role; Language Usage; Literacy; Navajo; Official Languages; Sociolinguistics; Spanish; New Mexico -- Palestine -- Paraguay -- Tonga -- Tongan; Reports, Research